Strategi Pengembangan Pariwisata Kawasan Geopark Meratus Provinsi Kalimantan Selatan, Studi Kasus: Kecamatan Piani Kabupaten Tapin - Magriaty, Riry (Journal of Regional and Rural Development Planning (Jurnal Perencanaan Pembangunan Wilayah dan Perdesaan), 2025)
Tourism has an important role in regional development. Tapin Regency in particular is part of the Meratus geopark because it is traversed by the Meratus mountainous landscape with geosites spread across parts of Piani District. This research examines the strategies and potential of new tourist destinations in the Meratus geopark lanskap. The results of the study show that the community supports tourism development in the Meratus Geopark area, especially if it is developed and focused on Piani District. Supported tourism is the organization of cultural events and the development of tourist attractions along the Meratus geopark route in Piani District. Nine new tourist locations were found that have the potential to become new tourist destinations in the region. In order for the Meratus geopark to be sustainable, the Regional Government must prioritize building access roads to tourist attractions, growing micro, small and medium enterprises and creating local specialty products, as well as increasing tourism cooperation with CSR. This strategy will have an impact on regional development, in the main to accelerate the development of the Meratus Geopark, Piani District, as a connecting route between strategic tourism areas.